NiOx‐Seeded Self‐Assembled Monolayers as Highly Hole‐Selective Passivating Contacts for Efficient Inverted Perovskite Solar Cells. Issue 11 (8th October 2021) - Sun, Juanjuan; Shou, Chunhui; Sun, Jingsong; Wang, Xinlong; Yang, Zhenhai; Chen, Ying; Wu, Jiarui; Yang, Weichuang; Long, Hanlin; Ying, Zhiqin; Yang, Xi; Sheng, Jiang; et al.
Abstract : Self‐assembled monolayers (SAMs) have emerged as effective carrier transport layers in perovskite (PVK) solar cells because of their unique ability to manipulate interfacial property, as well as simple processing and scalable fabrication. However, the defects and pinholes derived from their sensitive adsorption process inevitably deteriorate the final device performance. Herein, a sputtered nickel oxide (NiO x ) interlayer is used as a seed layer to promote the adsorption of the [2‐(3, 6‐dimethoxy‐9H‐carbazol‐9‐yl)ethyl]phosphonic acid (MeO‐2PACz) SAM on the indium tin oxide (ITO) substrate. The promoted adsorption is attributed to the enhanced tridentate binding between MeO‐2PACz and NiO x relative to the conventional bidentate binding between MeO‐2PACz and ITO. In addition, the NiO x modification can simultaneously improve the passivation ability and hole‐selectivity of the MeO‐2PACz, provide a favorable energy‐level alignment at the ITO/PVK interface, and prevent a direct contact between PVK and ITO. As a consequence, this NiO x ‐seeded MeO‐2PACz hole transport layer enables a significantly enhanced power conversion efficiency of 19.9% in comparison with 18.4% of the control device. This work provides an effective strategy to improve the performance of the SAM‐based photoelectric device. Abstract : A sputtered NiO x seed layer is employed to promote the adsorption of [2‐(3, 6‐dimethoxy‐9H‐carbazol‐9‐yl)ethyl]phosphonic acid (MeO‐2PACz) self‐assembled monolayers. The resulting high‐density MeO‐2PACz provides an increased passivation, an enhanced hole‐selectivity, a favorable energy‐level alignment, and a robust physical contact between perovskite and indium tin oxide. The corresponding inverted perovskite solar cell exhibits an impressive efficiency of 19.9%.